Improved phylogenetic resolution for Y-chromosome Haplogroup O2a1c-002611 - Xiaotian Yao (Nature Portfolio, 2017)
Abstract Y-chromosome Haplogroup O2a1c-002611 is one of the dominant lineages of East Asians and Southeast Asians. However, its internal phylogeny remains insufficiently investigated. In this study, we genotyped 89 new highly informative single nucleotide polymorphisms (SNPs) in 305 individuals with Haplogroup O2a1c-002611 identified from 2139 Han Chinese males. Two major branches were identified, O2a1c1-F18 and O2a1c2-L133.2 and the first was further divided into two main subclades, O2a1c1a-F11 and O2a1c1b-F449, accounting for 11.13% and 2.20% of Han Chinese, respectively. In Haplogroup O2a1c1a-F11, we also determined seven sublineages with quite different frequency distributions in Han Chinese ranging from 0.187% to 3.553%, implying they might have different demographic history. The reconstructed haplogroup tree for all the major clades within Haplogroup O2a1c-002611 permits better resolution of male lineages in population studies of East Asia and Southeast Asia. The dataset generated in the present study are also valuable for forensic identification and paternity tests in China.